The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s12034-019-1905-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of strontium-doped ZnS nanoparticles: structural, electronic and photocatalytic investigations

Abstract: Strontium-doped ZnS nanoparticles (NPs) (1.5, 5 and 9 wt%) were synthesized through a surfactant free hydrothermal method. The structural characterization by X-ray diffraction confirms the synthesis of ZnS, with its two crystalline phases (cubic and hexagonal), without apparition of any peaks related to Sr phases. The crystallite size is affected by Sr doping concentration and was estimated in the range of 2.24-2.51 nm. Furthermore, transmission electron microscopy images show that the NPs have great tendency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…We observe a decrease of the phonon energy , see Figure 7 , curves 3 and 4. A similar decrease of is reported in Sr-doped ZnS NPs by Boulkroune et al [ 31 ], where the radius of the Sr ion is larger compared to that of the Zn ion, i.e., there appears a tensile strain similar to the RE ion. Harish et al [ 41 ] have also observed a decrease of the transverse phonon mode with increasing Cu and Ce co-doping concentration.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…We observe a decrease of the phonon energy , see Figure 7 , curves 3 and 4. A similar decrease of is reported in Sr-doped ZnS NPs by Boulkroune et al [ 31 ], where the radius of the Sr ion is larger compared to that of the Zn ion, i.e., there appears a tensile strain similar to the RE ion. Harish et al [ 41 ] have also observed a decrease of the transverse phonon mode with increasing Cu and Ce co-doping concentration.…”
Section: Resultssupporting
confidence: 84%
“…Moreover, there are many published optical studies of different ion-doped (Cu, Mn, Ni, Co, Sr, V, Ag etc.) ZnS nanostructures [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. It is reported that the band gap increases with increasing TM doping concentration (Mn, Co, Ni, Cu, Ag, Cd) in ZnS NPs [ 30 ] and decreases with increasing Sr [ 31 ] or RE [ 34 , 35 ] dopants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks observe at 290cm -1 , 340cm -1 and 411cm -1 . The peaks around 275cm -1 represents transverse optical (TO) phonon mode as well as peak around 340cm -1 is assigned to longitudinal optical mode (LO) [49][50]. The peaks in between 275cm -1 and 340cm -1 were already reported by previous works and this is the characteristic of the ZnS-NPs [51][52].…”
Section: Optical Studiesmentioning
confidence: 72%
“…The high performance of SrTiO 3 in reaction to heterogeneous photocatalysis requires an effective architecture that maximizes the absorption of photons and reduces electron losses during excitation state (Coleto et al 2019;Ferreira et al 2020).Major efforts are required to further develop heterogeneous photocatalysis of SrTiO 3 under Ultraviolet, visible and solar illumination, in order to further improvement the transfer of charge carriers during excitation state. Actually, interesting and unique features of the binary photocatalyst mechanism have drawn more attention from researchers and have become a favorite subject of research among different groups of scientists across the globe (Ahlem et al 2018;Boulkroune et al 2019;Du et al 2021c, b). It was reported that the properties of the photocatalyst system depend primarily on the nature of the surface properties, the surface morphologies and the role of the optimum amount of doping incorporated in the SrTiO 3 (Hu et al 2020).…”
Section: Introductionmentioning
confidence: 99%